Perception about diabetes mellitus among college students aged between 18 and 25 years of Bengaluru city – A cross-sectional study - Maria Varghese; Deepthi N. Shanbhag; Merin Elizabeth Martin; George Mathew (International Journal of Noncommunicable Diseases, 2025)
Background: Globally, India ranks second in diabetes cases and is projected to reach 124 million by 2045. The average age of onset of diabetes in India ranges from 35 to 45 years. Aim/Objective: The study therefore aimed to assess the perception about diabetes mellitus among college students in Bengaluru city and identify the factors associated with their perception. Materials and Methods: A cross-sectional study was conducted among college students aged 18–25 years, studying courses such as engineering, science, law, arts, etc., in Bengaluru. The sample size calculated was 418, assuming a 56% prevalence of adequate knowledge regarding diabetes. A pretested, self-administered questionnaire was used to assess perception toward diabetes, including knowledge and attitude. Data were collected via Google Forms using the snowballing technique and analyzed using SPSS software. Results: Of the 422 participants (mean ± standard deviation [SD] age 20.2 ± 1.91 years, 52.6% females, 41% pursued science courses), 234 (55.5%) had heard of diabetes. Of the 234, about 64% thought that diabetes was preventable while 80% thought that it could spread from person to person, most (72.2%) were aware of the complications of diabetes, while 87% knew about treatment options. The mean ± SD knowledge and attitude scores in the 234 respondents were 19.32 ± 6.38 and 22.92 ± 2.90, respectively. Being female, studying science courses, and having family members with diabetes were factors significantly associated with higher knowledge scores and a positive attitude toward diabetes. Conclusion: The knowledge and attitude regarding diabetes among college students in Bengaluru city was limited and reflects an urgent need for interventions to improve them.